Criminal Law Perspectives on Final Project Making Services in Higher Education - Agung S, M Panji (Communication in Research and Publications (CRP), 2024)
This study examines the criminal law aspects of final project making services in higher education. The practice of students using third-party services to complete their final assignments has become increasingly prevalent, raising concerns about academic integrity and potential legal violations. Through a comprehensive literature review, this research explores the legal implications of such services, including fraud, document forgery, and copyright infringement. The study analyzes relevant laws and regulations in Indonesia, identifying regulatory gaps and challenges in law enforcement. It highlights the need for stricter legal policies and improved synergy between educational institutions, law enforcement, and government bodies to combat this issue effectively. The research aims to contribute to a deeper understanding of the criminal law dimensions of final project services and to encourage the development of more robust legal frameworks to preserve academic integrity in higher education.